The impact of artificial intelligence adoption digital marketing capabilities and firm performance: insghts from SMEs in El-oued - إيمان قدوده; بسمة صوالح محمد; الهام سعد العايب; خليفة الأرقط (university of eloued جامعة الوادي, 2024)
"هذه الدراسة تستقصي تأثير اعتماد الذكاء االصطناعي (AI (على قدرات التسويق الرقمي واألداء العام للمؤسسات الصغيرة والمتوسطة (SMEs (التي تعمل في قطاع الخدمات في مدينة الوادي بالجزائر. تتناول هذه الدراسة الفجوة البحثية في الدراسات االدبية القائمة، حيث تركز على قياس تأثيرات دمج الذكاء ، في قطاع الخدمات االصطناعي في سياق غير مبحوث بشكل جيد وتحديدا (SMEs (في اقتصاد نامي ً نتائج اعتماد التكنولوجيا. باستخ ً َّق جيدا حيث تبقى األدلة التجريبية نادرة ولم تُوث دام منهجية بحث كمي، جمعت الدراسة البيانات من خالل توزيع استبيانات منظمة لكبار المسؤولين التنفيذيين في مختلف صناعات قطاع الخدمات في الوادي. تم إجراء تحليل البيانات باستخدام 29 SPSS و4 PLS Smart ، مما يتيح التقييم الدقيق للعالقات المفترضة وضمان موثوقية وصحة النتائج البحثية. كشف التحليل عن وجود عالقة ذات داللة إحصائية بين اعتماد الذكاء االصطناعي مع قدرات التسويق الرقمي واعتماد الذكاء االصطناعي مع أداء الشركة. ومع ذلك، فإن تأثير قدرات التسويق الرقمي على األداء العام للشركة لم يظهر على أنه ذو داللة إحصائية. توصي الدراسة بإجراء بحوث إضافية الستكشاف المتغيرات الوسيطة التي تؤثر على العالقة المعقدة بين قدرات التسويق الرقمي المحسنة بواسطة الذكاء االصطناعي واألداء العام للمؤسسات الصغيرة والمتوسطة في سياقات مماثلة." "his study examine the influence of Artificial Intelligence (AI) adoption on the digital marketing capabilities and overall firm performance (Small and Medium- sized Enterprises) operating within the service sector of El Oued City, Algeria. Addressing a critical gap in the existing literature, this study focuses on quantifying the effects of AI integration within an under-researched context – specifically, service sector SMEs in a developing economy – where empirical evidence remains scarce and the outcomes of technological adoption are not well documented. Employing a quantitative research methodology, the study collected data through structured surveys administered to senior executives across various service sector industries in El Oued. Data analysis was conducted using SPSS 29 and Smart PLS 4, enabling rigorous evaluation of the hypothesized relationships and ensuring the reliability and validity of the research findings. The analysis revealed a statistically significant relationship between AI adoption with digital marketing capabilities and AI adoption with firm performance. However, the effect of digital marketing capabilities on overall firm performance presented a not significant relationship. The study recommends further research to explore the mediating variables that influence the complex relationship between AI-enhanced digital marketing capabilities and the overall firm performance in similar contexts."
Keywords: درات التسويق الرقمي; اعتماد الذكاء االصطناعي; اداء المؤسسة; المؤسسات الصغيرة و المتوسطة في قطاء الخدمات; الواد digital marketing capabilities; artificial intelligence adoption; firm performance; SMEs of service sector; Eloued